Sprint start kinematics during competition in elite and world-class male and female sprinters - Ciacci, S.; Merni, F.; Bartolomei, S.; Di Michele, R. (Journal of Sports Sciences, 2017)
The start kinematics has been reported to differ between male and female sprinters. This study aimed to determine whether kinematic differences between the sexes are attributable to an effect of sex per se, or rather to the absolute performance level of the sprinters, quantified by the 100-m time. A total of 20 sprinters (10 M, 10 F), including world-class and elite athletes, were assessed. Start phases from the "set" position to the first two steps were analysed. Linear regression analyses showed a few significant differences between sexes when taking into account the effect of performance level: M had shorter pushing phase duration, higher horizontal velocity at block clearing, and shorter contact times of the first two steps. Conversely, the performance level affected most of the examined parameters: faster sprinters showed the centre of mass (CM) closer to the ground and a more flexed front knee in the "set" position, longer pushing phase duration, lower vertical velocity of the CM at block clearing, and longer contact times and shorter flight times in the first two steps. These findings suggest that the start kinematics is only partially affected by the sex of sprinters, whereas a bigger role is played by their performance level.